2018
DOI: 10.1590/1516-3180.2018.0061240418
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between premenstrual syndrome and basic personality traits: a cross-sectional study

Abstract: This study demonstrates that personality may be associated with premenstrual syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
1
22
1
1
Order By: Relevance
“…Of all the students who accepted to participate in the study, 73.1% were female and 33.2% were fourth-year students; average age was 20.70 ± 1.93 (min-max, [17][18][19][20][21][22][23][24][25][26][27][28][29]; and average number of siblings was 4.52 ± 2.13. In addition, 55.1% of the mothers graduated from primary school, and 41.2% of the fathers graduated from secondary school.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all the students who accepted to participate in the study, 73.1% were female and 33.2% were fourth-year students; average age was 20.70 ± 1.93 (min-max, [17][18][19][20][21][22][23][24][25][26][27][28][29]; and average number of siblings was 4.52 ± 2.13. In addition, 55.1% of the mothers graduated from primary school, and 41.2% of the fathers graduated from secondary school.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that according to the CPS subscale mean scores, the participants had more extraverted and more emotionally unstable personality traits. A study that investigated the relationship between university students' premenstrual syndrome and personality traits showed that according to the CPS subscale mean scores, the students had extraverted and emotionally unstable personality traits; and the students who had unstable personality traits experienced premenstrual syndrome symptoms more intensively . A study conducted by Bal and Şahin with women in menopausal period reported that the CPS subscale mean score indicated women having introverted and emotionally unstable personality traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epilepsy). Other psychologic and behavioural PMS symptoms include: sugar and salt cravings, tension or anxiety, irritability, crying and tearfulness, fatigue, depressed mood, insomnia or hypersomnia, forgetfulness or confusion, panic attacks, aggression and depression [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There is also no evidence comparing acupuncture or acupressure with currently recommended therapies for PMS, such as selective serotonin reuptake inhibitors (SSRIs). Further research is necessary, using approved measures for PMS, appropriate blindness and appropriate comparative groups reflecting the best practice currently [30].…”
Section: Premenstrual Syndrome (Pms)mentioning
confidence: 99%